The Strategic Leader's Roadmap : 6 Steps for Integrating Leadership and Strategy - Singh, Harbir; Useem, Michael (Wharton School Press, 2021)
In The Strategic Leader's Roadmap, Updated and Revised Edition: 6 Steps for Integrating Leadership and Strategy, Wharton management professors Harbir Singh and Michael Useem offer a six-point checklist for today's leaders to follow. They explain how leading strategically will help managers strengthen their capacity to develop strategy and to lead its execution.